(3UhGf GdMceIs - (3Ydj Hf RjO Hf eMeO Hf GdMSjf, CHh GdMSf, XgjQ GdOjf, GdHjgbj, hjbGd dg GHf afOb,J (B565 (3g` s
(3ChdgG (B:s
(3Cf JhbYhG Ydi GdChd TjFkG eGdGTc Cfg ZjQ dGjb Hg hbGd ai QSGdJg Edi OjGSjhT s
(3BNQgG (B:s
(3aQW GdMQGQI Ch GdHQhOI hEeG GdSadjI aGf jchf HQjI HMQjI SgdjI LHdjI s
(3HgG XGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B290 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B96s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs